The Heterogeneous Effect of Digitizing Community Activities on Community Participation - Martina Pocchiari; Jason M.T. Roos (Center for Economic Studies and ifo Institute (CESifo), 2023)
As social and business activities undergo significant digital transformation, the allure of digitized versus traditional in-person events remains a critical question. This study quantifies the heterogeneous effect of digitization on community participation across communities catering to different interests, such as business, technology, and socialization. Leveraging comprehensive panel data from a leading community-building platform, our analyses reveal that prospective participation in digitized events is lower compared to their in-person counterparts. However, this overarching effect masks a more complex reality. We uncover significant heterogeneity in participation intentions, with outcomes closely tied to specific event characteristics and interest topics. For example, prospective engagement in digitized networking meetings varies substantially depending on whether the meetings are business- or leisure-oriented. Similarly, the context in which goal-oriented meetings occur plays a decisive role: prospective participation in digitized events decreases by 2.95% for writing clubs, but increases by 2.72% for language clubs. These findings suggest that approaches to community-building through digitization must be tailored to the unique attributes of the community and its events. A one-size-fits-all strategy to digital transformation may fall short of fostering meaningful engagement. As the digital landscape evolves, our research offers quantitative benchmarks and managerial guidelines for community engagement in the digital age.
Keywords: M31; M10; 330